Jasmine and stars : reading more than Lolita in Tehran - Keshavarz, Fatemeh (Islamic civilization & Muslim networks, 2007)
In a direct, frank, and intimate exploration of Iranian literature and society, scholar, teacher, and poet Fatemeh Keshavarz challenges popular perceptions of Iran as a society bereft of vitality and joy. Her fresh perspective on present day Iran provides a rare insight into this rich but virtually unknown culture alive with artistic expression. Keshavarz introduces readers to two modern Iranian women writers whose strong and articulate voices belie the stereotypical perception of Iranian women as voiceless victims in a country of villains. She follows with a lively critique of the best-sellingReading Lolita in Tehran: A Memoir in Books, which epitomizes what Keshavarz calls the "New Orientalist narrative" marred by stereotype and prejudice more often tied to current geopolitical conflicts than to an understanding of Iran. Blending in firsthand glimpses of her own life from childhood memories in 1960s Shiraz to her present life as a professor in America Keshavarz paints a portrait of Iran depicting both cultural depth and intellectual complexity. With a scholar's expertise and a poet's hand, she helps amplify the powerful voices of contemporary Iranians and leads readers toward a deeper understanding of the country's past and present.
Keywords: Nafisi, Azar : Reading Lolita in Tehran; Farrukhzād, Furūgh : Criticism and interpretation; Pārsīʹpūr, Shahrnūsh : Criticism and interpretation; Persian literature : Women authors : History and criticism; Persian literature : 20th century : History and criticism; Persian literature : 21st century : History and criticism